Gender Harmony and Household Integrity in Migrant Worker Families in Ponorogo: A Sociological Analysis - Andhita Risko Faristiana; Muchlis Daroini (MUWAZAH : jurnal kajian gender, 2025)
This research analyzes the dynamics of gender harmony and household integrity in migrant worker families in Ponorogo through a qualitative case study approach. The feminization of international migration creates complex gender role restructuring that involves negotiation between Javanese cultural values, Islamic religiosity norms, and the practical demands of transnational life. The findings reveal heterogeneity in family adaptive responses, where the redistribution of domestic roles ranges from progressive transformation to the perpetuation of patriarchy, influenced by individual gender literacy, social stigma, and the quality of digital communication. Although women*'s** economic contributions increase their bargaining power, conservative gender ideology perpetuates the double burden and relational inequality. Family resilience is determined by the convergence of extended family support, remittance management strategies, legal literacy, and religiosity as a coping mechanism. The research identifies gaps in legal protection, risks of family disintegration due to boundary ambiguity, and the transformation of younger generation aspirations. The theoretical implications enrich the transnational family sociology discourse with local cultural perspectives, while practical recommendations include developing a holistic protection framework that integrates gender-sensitive pre-departure counseling, the strengthening of community networks, and sustainable empowerment programs.